Premovement inhibition can protect motor actions from interference by response irrelevant sensory stimulation. - McInnes, Aaron Nicholas; Lipp, Ottmar V; Tresilian, James R; Vallence, Ann-Maree; Marinovic, Welber (2021)
KEY POINTS: